Cloud Infrastructure Transformation in Healthcare: A Comprehensive Analysis of Applications, Benefits, and Implementation Challenges - Sardar Mohammed (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rapid evolution of cloud infrastructure in healthcare represents a transformative shift in how medical institutions deliver, manage, and optimize patient care services. This comprehensive article examines the integration of cloud-based solutions across diverse healthcare organizations, analyzing the multifaceted impact on operational efficiency, patient care outcomes, and technological capabilities. Through extensive article research combining quantitative performance metrics with qualitative stakeholder insights, this study reveals significant improvements in electronic health record management, telemedicine capabilities, and artificial intelligence integration, while addressing critical security and compliance requirements. The article demonstrates substantial enhancements in operational efficiency, cost reduction, and healthcare service delivery, with organizations achieving meaningful returns on investment and improved patient care capabilities. While acknowledging implementation challenges such as technical barriers, security concerns, and staff training requirements, the article indicates that cloud infrastructure adoption in healthcare yields considerable benefits and positions organizations for future technological advancement. The article concludes that successful cloud integration is essential for modern healthcare delivery, enabling enhanced patient care coordination, improved diagnostic capabilities, and streamlined operational processes, ultimately contributing to a more efficient and responsive healthcare ecosystem.